2016
DOI: 10.1186/s12905-016-0309-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of obstetric danger signs and associated factors among pregnant women in Erer district, Somali region, Ethiopia

Abstract: BackgroundKnowledge of danger signs of obstetric complications is first step in the appropriate and timely referral to essential obstetric care. Although women’s knowledge about the obstetric danger signs is important for improving maternal and child health, little is known about the current knowledge and influencing factors in pastoral community of Ethiopia. This study, therefore, aims to fill this gap by assessing the current level of knowledge and associated factors of pregnant women living in Erer district… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
71
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 9 publications
13
71
4
4
Order By: Relevance
“…7,14 Also, in consistence with previous studies conducted in Ethiopia, Malaysia and Nigeria, a good level of awareness on danger signs was significantly associated with higher educational levels of both pregnant mother and her husband and employment status of the pregnant mother. 7,9,11,13,14 As these variables are somewhat interconnected, the observed associations could be due to potential confounding effect mediated through high maternal health literacy.…”
Section: The Association Between the Level Of Awareness And Basic Chamentioning
confidence: 99%
See 4 more Smart Citations
“…7,14 Also, in consistence with previous studies conducted in Ethiopia, Malaysia and Nigeria, a good level of awareness on danger signs was significantly associated with higher educational levels of both pregnant mother and her husband and employment status of the pregnant mother. 7,9,11,13,14 As these variables are somewhat interconnected, the observed associations could be due to potential confounding effect mediated through high maternal health literacy.…”
Section: The Association Between the Level Of Awareness And Basic Chamentioning
confidence: 99%
“…Results comparable to the present study were observed in some settings, 14 whereas in other settings a significantly higher knowledge of danger signs was observed among urban population. 8,9 This difference could be partially explained by the marked discrepancy of the accessibility of health care and availability of other facilities such as electronic media between different sectors in those countries. 15 Contrary to the findings of studies conducted in Northwest and Somali regions of Ethiopia, a higher proportion of primi mothers in this study had a good knowledge of danger signs compared to multiparous mothers.…”
Section: The Association Between the Level Of Awareness And Basic Chamentioning
confidence: 99%
See 3 more Smart Citations